A review of chemical looping reforming technologies for hydrogen production: recent advances and future challenges - Rouzbeh Ramezani; Luca Di Felice; Fausto Gallucci (JPhys Energy, 2023)
Faced with increasingly serious energy and global warming, it is critical to put forward an alternative non-carbonaceous fuel. In this regard, hydrogen appears as the ultimate clean fuel for power and heat generation, and as an important feedstock for various chemical and petrochemical industries. The chemical looping reforming (CLR) concept, is an emerging technique for the conversion of hydrocarbon fuels into high-quality hydrogen via the circulation of oxygen carriers which allows a decrease in CO _2 emissions. In this review, a comprehensive evaluation and recent progress in glycerol, ethanol and methane reforming for hydrogen production are presented. The key elements for a successful CLR process are studied and the technical challenges to achieve high-purity hydrogen along with the possible solutions are also assessed. As product quality, cost and the overall efficiency of the process can be influenced by the oxygen carrier materials used, noteworthy attention is given to the most recent development in this field. The use of Ni, Fe, Cu, Ce, Mn and Co-based material as potential oxygen carriers under different experimental conditions for hydrogen generation from different feedstock by CLR is discussed. Furthermore, the recent research conducted on the sorption-enhanced reforming process is reviewed and the performance of the various type of CO _2 sorbents such as CaO, Li _2 ZrO _3 and MgO is highlighted.